Treatment of diseases associated with non-cicatricial alopecia - Lidia Rudnicka; Agnieszka Kaczorowska (Przegląd Dermatologiczny, 2022)
Alopecia (loss of volume or complete loss of hair) can be a symptom of many diseases. In some cases it is a symptom of a local pathology limited to the scalp, in others it is a dermatological symptom of a systemic pathology. In almost every case, alopecia has a significant impact on the quality of life and may cause limitations in professional, social and private life. The management of alopecia is based on a preceding comprehensive medical differential diagnosis, which significantly exceeds basic dermatological diagnostic procedures. This article presents the basic information on therapeutic methods that can be used in selected diseases associated with non-cicatricial alopecia: androgenetic alopecia, senile alopecia, anagen effluvium, telogen effluvium, alopecia areata, non-cicatricial alopecia secondary to systemic lupus erythematosus, trichotillomania, traction alopecia, pressure alopecia, lipedematous scalp and lipedematous alopecia.